Development of Weebly-Based Learning Media Utilizing Flipped Classroom and Team Games Tournament Approaches for Petroleum Topics - Asrifaturofingah, Asrifaturofingah; Zamhari*, Muhammad (Jurnal IPA & Pembelajaran IPA, 2024)
The national curriculum seeks to create engaging, student-focused learning experiences. Despite this, chemistry education, particularly on petroleum topics, often relies on traditional methods such as lectures and printed materials, which fail to foster active student involvement. Consequently, there is a need to develop learning strategies that align with the curriculum's goals. This study focuses on creating and assessing the quality of Weebly learning media, utilizing a flipped classroom approach and teams games tournament for teaching petroleum content. The method applied in this study is Research and Development, by using the ADDIE (analysis, design, development, implementatio, evaluation) model. However, in this study the implementation stage was not carried out. The study's participants included three peer reviewers, a material expert validator, a media expert validator, five chemistry teachers from high schools, and thirteen high school students. Data was gathered using a questionnaire, which an instrument specialist had validated. The data obtained were analyzed descriptively qualitatively and descriptively quantitatively. The results of this study showed positive results with a material expert assessment score of 94.11% (very good), a media expert assessment of 85.96% (very good), a reviewer score of 94.56% (very good) and a respondent score of 94.87%. This study demonstrates that the developed learning media is of high quality and effectively supports chemistry education in schools, particularly on petroleum topics.